Multi‐Functional Bio‐HJzyme: Revolutionizing Diabetic Skin Regeneration with its Glucose‐Unlocked Sterilization and Programmed Anti‐Inflammatory Effects - Miaomiao He; Zuyao Wang; Hang Yang; Qiancun Wang; Danni Xiang; Xinyan Pang; Yau Kei Chan; Dan Sun; Guangfu Yin; Weizhong Yang; Yi Deng (Advanced Science, 2023)
Abstract Antibacterial dynamic therapy (ADT) triggered by reactive oxygen species (ROS) is promising for diabetic infectious disease treatment. However, the limited local O2/H2O2 production and post‐treatment inflammation remain long‐standing issues. To address these challenges, a novel H2‐evolving bio‐heterojunction enzyme (Bio‐HJzyme) consisting of graphite‐phase carbon nitride/copper sulfide (CN/Cu2−xS) heterojunction and glucose oxidase (GOx) is created. The Bio‐HJzyme offers glutathione peroxidase (GPx), peroxidase (POD), and catalase (CAT) mimetic activities; provides anti‐pathogen properties via programmed light activation; and effectively promotes diabetic wound healing. Specifically, its GPx‐mimetic activity and the presence of GOx significantly enhance the yield of H2O2, which can be catalyzed through POD‐mimetic activity to produce highly germicidal •OH. The H2O2 can also be catalyzed to H2O and O2, assisted by the CAT‐mimetic activity. The catalyzed products can then be catalyzed into germicidal •OH and •O2− under NIR light irradiation, giving enhanced ADT. Further, CN can split water to form H2 under solar light, which dramatically suppresses the inflammation caused by excessive ROS. In vivo evaluation confirms that Bio‐HJzyme promotes the regeneration of diabetic infectious skin through killing bacteria, enhancing angiogenesis, promoting wound bed epithelialization, and reinforcing anti‐inflammatory responses; hence, providing a revolutionary approach for diabetic wounds healing.